2002
DOI: 10.1103/physreve.65.051805
|View full text |Cite
|
Sign up to set email alerts
|

Competition of mesoscales and crossover to tricriticality in polymer solutions

Abstract: We show that the approach to asymptotic fluctuation-induced critical behavior in polymer solutions is governed by a competition between a correlation length diverging at the critical point and an additional mesoscopic length-scale, the radius of gyration. Accurate light-scattering experiments on polystyrene solutions in cyclohexane with polymer molecular weights ranging from 200,000 up to 11.4 million clearly demonstrate a crossover between two universal regimes: a regime with Ising asymptotic critical behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…For ξ + 0 , values obtained from turbidity measurements by Zhou et al [14] and Beysens et al [15] as well as those determined from ellipsometry [16] and 3 Critical amplitudes of (a) the specific heat capacity per unit volume A + v and (b) the correlation length ξ + 0 for NB-C N H 2N +2 critical mixtures. Open circles [5], open squares [6], black circles this work, open triangles [11], open diamonds [12], stars [13], and crosses [14] X-ray scattering [17] are also represented in (b). As can be observed, A + v hardly varies with N; indeed, our A + v value for N = 14 is consistent with the trend inferred from the behavior of mixtures with lower alkanes [7,8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For ξ + 0 , values obtained from turbidity measurements by Zhou et al [14] and Beysens et al [15] as well as those determined from ellipsometry [16] and 3 Critical amplitudes of (a) the specific heat capacity per unit volume A + v and (b) the correlation length ξ + 0 for NB-C N H 2N +2 critical mixtures. Open circles [5], open squares [6], black circles this work, open triangles [11], open diamonds [12], stars [13], and crosses [14] X-ray scattering [17] are also represented in (b). As can be observed, A + v hardly varies with N; indeed, our A + v value for N = 14 is consistent with the trend inferred from the behavior of mixtures with lower alkanes [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…1 has been checked for a wide variety of binary mixtures via the experimental determination of α and some universal relations involving A ± [4]. Nevertheless, some specific liquid-liquid systems are problematic because their A ± values are extremely small: two examples are Coulombic ionic solutions [5] and polymer solutions [6]. It is therefore interesting to test how sensitive current experimental methods for determining A ± can be.…”
Section: Introductionmentioning
confidence: 99%
“…In the asymptotic vicinity of the critical point, the correlation length becomes much larger than the radius of gyration and the polymer solution exhibits Ising critical behavior. With increase of the polymer molecular weight and, hence, of the radius of gyration, the range of asymptotic Ising critical behavior shrinks, ultimately yielding to theta-point tricritical behavior [2]. This competition of two mesoscales arises from a coupling between two different order parameters belonging to two different static universality classes, namely, one associated with phase separation and another one with self-avoiding-walk singularities of long polymer chains [3].…”
Section: 41+ementioning
confidence: 99%
“…However, we have found that this mode being trapped by the entanglements, may become an order slower as compared to uncoupled critical slowdown. Moreover, the diffusivity, like static properties [2], exhibits crossover from critical (Ising) to theta-point tricritical (mean-field) behavior, becoming almost "classical" at the highest molecular weight. In fact, the coupling of two modes and the crossover to tricriticality are just two sides of the same physical phenomenon, caused by an interaction of two order parameters resulting in the emergence of a tricritical point.…”
Section: 41+ementioning
confidence: 99%
“…The micelles set a mesoscopic scale in the system that can compete with the correlation length of the critical fluctuations. This fact may originate a complex crossover behaviour from mean-field to Ising behaviour [41][42][43][44]. While the existing experimental data are still somewhat contradictory for the crossover of bulk properties [42,43,45,46], no specific experimental search for the crossover effect on the interfacial properties has been reported yet.…”
Section: Introductionmentioning
confidence: 99%